The Role of MTs N 3 Surabaya City in Building Religious Moderation Culture: Analysis of Inclusive and Child-Friendly Education Models - Asmiati, Asmiati; Atmaja, Dwi; Mahmudah, Lilik; Kholiq, Abdul; Widyanto, Priyo Bagus (Jurnal Edusci, 2025)
Backgrounds. As educational institutions with Islamic characteristics, madrasahs play unique roles and bear special responsibilities in this national project. Madrasahs function not only as institutions for knowledge transfer, but also as centers for character formation and religious understanding of Indonesia's young Muslim generation. Aims. This research conducts an in-depth analysis of the religious moderation culture development model at MTsN 3 Surabaya City, positioned as a pioneer in responding to the national agenda for strengthening religious moderation. Facing challenges of intolerance and radicalism, this madrasah has designed a holistic and systematic program architecture. Methods. Using qualitative analysis methods on institutional publication data and news reports, this study identifies three main strategic pillars: (1) student empowerment as agents of change through the flagship program "Young Ambassadors of Religious Moderation"; (2) institutional ecosystem strengthening through in-depth teacher training and internal knowledge production in the form of dozens of moderation books; and (3) holistic integration of moderation values into curriculum, school culture, and strategic partnerships. Result. The main findings indicate that this strategy not only successfully forms tolerant, prosocial, and nationally minded student characters, but also fundamentally transforms the school climate into a safer, more harmonious, and collaborative environment. Conclusion. The central thesis of this report is that the comprehensive implementation of religious moderation at MTsN 3 Surabaya City functions as an instrumental mechanism to realize an inclusive education model based on the Child-Friendly School (CFS) framework. Implementation. This model proves effective in translating macro policies into impactful micro practices, offering valuable insights for other educational institutions.